Teleopieka, wspólnoty mieszkań dla seniorów oraz międzypokoleniowe współlokatorstwo, czyli alternatywne formy opieki i wspierania osób starszych - Ulaniecka, Natalia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
This article presents examples of alternative forms of support for the elderly. The first part presents the concept and use of telecare - the information and communication system, which monitors the situation of senior and alerts in case of danger. The second part contain the advantages and disadvantages of senior cohousing. The third part is about popular in Spain and France the idea of intergenerational (senior and student) home-sharing and analysis capabilities to popularize this solution in Poland.